PROMOTING GREENING AND GREEN JOBS THROUGHOUT THE CRISIS – THE CASE OF ROMANIA - Ghinararu, Catalin (Annals of Spiru Haret University. Economic Series, 2013)
The article focuses on the issues of green jobs and the promotion of green economy in Romania. It takes over several developments throughout the years of crisis pointing both to the progresses made as well as to the hindrances brought about by the economic depression to the efforts of developing a green sector in an emergent economy. A special part is dedicated to actions and initiatives financed via the structural and cohesion instrument as well as to the impact of various initiatives under the EU 2020 Strategy. An analysis is carried out on these initiatives, their number, their character and relative effectiveness. The article also focuses on general aspects relating to greening of the economy and the growing use of renewable resources.